(untitled) (Discourse of Law and Administration, 2023)
The author analyzed the legitimacy of the constitutionalisation of the State Commission. The observation of the activities of the democratic state institutions made us reflect once again on the need or even justifiability of assigning the status of a constitutional body to the NEC. The conclusion of the considerations introduces the postulate to raise to the rank of constitutional State Electoral Commission, which is an organ of state control and protection of the law. The constitutional foundation is extremely important for the structure and composition of the electoral bodies. The analysis of the tasks of the NEC proves that the constitutionalization of this central electoral body, supervising the implementation of passive and active electoral law, and of a body independent of the executive, seems to be necessary in the light of its current competences.